ASSESSMENT OF THE EFFECTIVENESS OF ANALGESIA AFTER UPPER EXTREMITY SURGERY IN CHILDREN WITH ULTRASOUND-GUIDED BRACHIAL PLEXUS BLOCKS AT NGHE AN OBSTETRIC AND PEDIATRIC HOSPITAL FROM 02/2022 TO 10/2022 (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the effectiveness of analgesia after upper extremity surgery in childrenwith ultrasound-guided brachial plexus blocks.Subjects-methods: 54 pediatric patients undergoing upper extremity surgery, eligible forselection, were randomly assigned to 2 groups: General anesthesia with ultrasound-guided brachialplexus blocks (group I) or general anesthesia (group II).Results: Showed that Ramsay's sedation score after surgery: Group I had 100% of patientsachieved ≤3, group II had 85.18% achieved ≤ 3 and 14.82% patients achieved 4 points (p
Keywords: Supraclavicular brachial plexus blocks, ultrasound-guided, analgesia, children.